A Simple Time Series Test of Endogenous vs. Exogenous Growth Models: An Application to the United States - Kocherlakota, Narayana R.; Yi, Kei-Mu (The Review of Economics and Statistics, 1996)
Narayana R. Kocherlakota, Kei-Mu Yi, A Simple Time Series Test of Endogenous vs. Exogenous Growth Models: An Application to the United States, The Review of Economics and Statistics, Vol. 78, No. 1 (Feb., 1996), pp. 126-134